Successful outcomes in childrens specialist weight management: Impact assessment of a novel early years weight management programme. Issue 5 (24th April 2021) - Tee, Louise P.; Brandreth, Rachael A.; Sauven, Natasha; Clarke, Lia; Frampton, Ian
Abstract: Background: In the UK, more than one in five children are overweight on starting school. An elevated body mass index (BMI) in childhood increases the likelihood of developing many health and social issues. The Lifestyles, Eating and Activity for Families (LEAF) programme is a weight management service for clinically obese children under the age of 7 years and their families. This study evaluates the effectiveness of the LEAF programme by measuring BMI z ‐score change, the reduction in calorific beverage consumption and user satisfaction. Methods: Data were collected over 6 years from 2012 and children who met the local weight management pathway criteria were recruited. Contact time was typically 20 h over 12 months and included home and clinic‐based assessment by the multidisciplinary team and community‐based intervention through six group sessions. This study compared baseline and post‐intervention BMI z ‐scores (zBMI) for 65 children, as well as daily total calorific intakes from beverages for 41 children, and, in addition, 20 parents completed user satisfaction questionnaires. Results: There was a highly significant reduction in both mean zBMI (0.5; p  < 0.001) and mean total calories from beverages (199; p  < 0.001) across the intervention period. There was no significant correlation between zBMI and beverage calorific trends. Families who completed user satisfaction questionnaires reported that they had changed their dietary habits and 90% would recommend the programme to others. Conclusions: This initial evaluation indicates that the LEAF programme was effective in reducing the zBMI of a group of clinically obese young children. Keywords obesity epidemic, young children, intervention, multidisciplinary Abstract :